2011
DOI: 10.1007/s10337-011-2037-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinic Pharmacokinetic Profiles of Huperzine A Following Transdermal Administration to Healthy Human Volunteers

Abstract: To support the rationale behind the development of the huperzine A patches and its pharmacological effects in clinical therapy, an LC-MS-MS method was developed and validated for determination of huperzine A in human plasma and then applied to the clinic pharmacokinetics study on transdermal patches of huperzine A. After a simple liquid-liquid extraction with ethyl acetate, analytes were separated on a C18 column with isocratic elution. The detection of analytes was performed on a tandem mass system equipped w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…One common disadvantage of the traditional transdermal system is the low bioavailability. Therefore, sufficient medicine is required as the penetration force, and a large amount of the medicine still remains after wearing (Ye et al., 2008 ; Wu et al., 2011 ; Amjadi et al., 2018 ; Lee & Prausnitz, 2018 ). Results in this study indicated that DMNP can prolong the elimination of t 1/2 and enlarge the area under the curve (AUC), presenting a higher relative bioavailability value than that of oral administration.…”
Section: Resultsmentioning
confidence: 99%
“…One common disadvantage of the traditional transdermal system is the low bioavailability. Therefore, sufficient medicine is required as the penetration force, and a large amount of the medicine still remains after wearing (Ye et al., 2008 ; Wu et al., 2011 ; Amjadi et al., 2018 ; Lee & Prausnitz, 2018 ). Results in this study indicated that DMNP can prolong the elimination of t 1/2 and enlarge the area under the curve (AUC), presenting a higher relative bioavailability value than that of oral administration.…”
Section: Resultsmentioning
confidence: 99%